Effect of hypoxia severity on periphal fatigue development and subsequent exercise performance during exhaustive intermittent cycling - Christian, R.; Racinais, S.; Buchheit, M.; Girard, O. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Under acute severe hypoxia, central nervous system fatigue may limit performance during high-intensity continuous exercise, while also curtailing the extent of peripheral fatigue development. Whether this scenario occurs during whole body high-intensity, intermittent exercise is unknown. The aim of this study was to examine the effect of hypoxia severity on peripheral fatigue development and subsequent exercise performance during exhaustive intermittent cycling. Eleven well-trained cyclists performed an intermittent cycling exercise until exhaustion in different levels of hypoxia (set 1) followed 30 min latter by the same exercise to exhaustion in normoxia (set 2). Each set consisted of the maximum number of sprint bouts - 15 s at 30% of the anaerobic power reserve (643±38 W) with a fixed pedaling frequency of 110 rpm. Set 1 was performed under normoxic (simulated altitude/end-exercise arterial O2 saturation = 0 m/96%), moderate (2200 m/90%) and severe hypoxic (4200 m/79%) conditions, in a counterbalanced order. Maximal isometric voluntary contractions of the knee extensors (MVC torque) and mechanical responses to supra-maximal femoral nerve stimulations (peak twitch torque) were obtained at rest and 7 min after each set. During set 1, performance was dependent on hypoxia severity (23 ± 9, 16 ± 6 and 10 ± 3 sprint repetitions in normoxia, moderate and severe hypoxia, respectively; p<0.001), whereas the number of sprint bouts completed did not differ during set 2 (12± 6, 14 ± 8, 18± 15; p>0.49). Compared with baseline, reductions in peak twitch amplitude post-set 1 were of similar magnitude among all conditions (-53.0%, all conditions compounded; p<0.001), without any further changes following set 2. At exhaustion following set 1, strength loss compared to baseline was similar among the normoxic and moderate hypoxic conditions (-10.8% and -11.4%; both p<0.05), while it tended to be smaller in severe hypoxia (-8.7% p=0.057). However, voluntary strength capacity was further decreased in all conditions after set 2 (-5.7%, all conditions compounded; p<0.05). Despite performance being hypoxia severitydependent during the first set, there was no significant performance difference in a subsequent normoxic exercise of the same nature. At task failure, peripheral fatigue was substantial compared with baseline but similar across conditions, which was associated with rather consistent decreases in voluntary strength. After set 2, voluntary strength was further decreased in all conditions despite no additional peripheral fatigue development. These results suggest that an end-exercise arterial O2 saturation value of 79% or above is probably not severe enough to elicit a shift from a predominantly peripheral origin of fatigue to a hypoxia-sensitive source of inhibition within the central nervous system.